Silverlight 2 recipes : a problem-solution approach - Ghosh, Jit (Expert's voice in .NET., 2008)
"Silverlight 2 Recipes: A Problem-Solution Approach is for every Silverlight developer. The book covers all aspects of Microsoft Silverlight including the programming model, browser integration, integration with server side technologies such as web services, and specific sections on rich media integration. All developers and architects looking for a .NET-based platform to deliver rich interactivity and media to their consumers, with deep integration with the rest of their technology stack, will find Silverlight 2 Recipes: A Problem-Solution Approach a must-have guide."--Jacket